1989
DOI: 10.1111/j.1476-5381.1989.tb11885.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the structure‐activity relationships of a series of analogues of mephenesin and strychnine on the response to pressure in mice

Abstract: AB9 lAS 1 A range of compounds structurally related to the centrally acting muscle relaxant mephenesin and to the chemical convulsant strychnine were synthesized and tested for their ability to alter the threshold pressures for the onset of high pressure convulsions in mice. 2 The ability of both groups of compounds to alter the threshold pressures for convulsions was found to be dependent on the nature of a simple molecular skeleton. Thus, compounds that possessed a negatively polarized group located both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…That large pressures (of the order of 10 MPa) will antagonize general anaesthesia [38] led to a theory of general anaesthesia that assumed that anaesthetics and pressure acted at a common site and via a common mechanism [47]. More recently it was observed that species diat do not use glycine as a neurotransmitter do not exhibit pressure reversal of anaesthesia [72] and that pressure, far from acting in a non-specific manner, appears to act in a highly selective way [10,11,71]. At the level of the neurotransmitter receptor-ion channel complex, it has been shown that the kainate channel is unaffected by pressure but that the glycine channel is highly pressure sensitive [16,69].…”
Section: Discussionmentioning
confidence: 99%
“…That large pressures (of the order of 10 MPa) will antagonize general anaesthesia [38] led to a theory of general anaesthesia that assumed that anaesthetics and pressure acted at a common site and via a common mechanism [47]. More recently it was observed that species diat do not use glycine as a neurotransmitter do not exhibit pressure reversal of anaesthesia [72] and that pressure, far from acting in a non-specific manner, appears to act in a highly selective way [10,11,71]. At the level of the neurotransmitter receptor-ion channel complex, it has been shown that the kainate channel is unaffected by pressure but that the glycine channel is highly pressure sensitive [16,69].…”
Section: Discussionmentioning
confidence: 99%
“…Structure activity relationships triggered this study; the test drugs used being modelled on the strychnine molecule and in particular a negatively charged group spaced 4.5 angstroms from an aromatic group (Bowser-Riley et al, 1989b), but it transpired that this shows marked similarities to the more recently proposed antagonist pharmacophore at the SIglycine site associated with the NMDA receptor (Moselley et al, 1992;Kemp & Leeson, 1993). The benzimidazole derivative closely fits the model whereas gramine clearly does not.…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…In the present study we have chosen to investigate three test drugs; (i) a benzimidazole derivative which shows the clearest structural similarities to known SI-glycine site antagonists and is also effective against HPNS (Helliwell, 1990); (ii) gramine which has the opposite effect and facilitates HPNS (Bowser-Riley et al, 1989b) and (iii) mephenesin which is the most effective drug against HPNS (Bowser-Riley et al, 1989b). We have also compared the effects of these drugs with those of the competitive NMDA antagonist D-2-amino-5-phosphonovalerate (AP5), and a known antagonist at the SI-glycine site, 7-chlorokynurenic acid (7CK).…”
Section: Introductionmentioning
confidence: 99%